2013
DOI: 10.1177/1035304613496500
|View full text |Cite
|
Sign up to set email alerts
|

Temporary migrant nurses in Australia: Sites and sources of precariousness

Abstract: Temporary migrant workers are widely regarded as a precarious group of workers. This precariousness is often traced back to the sphere of employment, though recent research also points to the implications of the limited rights entailed by temporary migrant status. This article draws on empirical work among registered nurses who have participated in the Australian 457 visa scheme -the major programme for temporary migrant workers in Australia. Using a range of empirical sources, including in-depth interviews wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Vulnerability to exploitation by employers, intermediary agents, education providers and other actors has emerged as a common issue across most temporary visa categories in Australia (see, for example, Biao 2007;Nyland et al 2009;Bertone 2013, 179;Velayutham 2013;Boese et al 2013;Robertson 2015;Berg 2016;Tham et al 2016). Immigration policy settings, such as the increased emphasis on employer-sponsorship in the permanent skilled migration program, can condition pathways between visas in ways that exacerbate migrant precarity by increasing dependence on employers (Productivity Commission 2015, 382-3).…”
mentioning
confidence: 99%
“…Vulnerability to exploitation by employers, intermediary agents, education providers and other actors has emerged as a common issue across most temporary visa categories in Australia (see, for example, Biao 2007;Nyland et al 2009;Bertone 2013, 179;Velayutham 2013;Boese et al 2013;Robertson 2015;Berg 2016;Tham et al 2016). Immigration policy settings, such as the increased emphasis on employer-sponsorship in the permanent skilled migration program, can condition pathways between visas in ways that exacerbate migrant precarity by increasing dependence on employers (Productivity Commission 2015, 382-3).…”
mentioning
confidence: 99%
“…Those with qualifications or professional experience from a small group of largely English-speaking countries as well as Singapore, Hong Kong and some EU countries, are able to obtain off-shore registration. For those from other countries, a number of barriers have to be overcome -English language tests and a bridging or conversion course -which means that they are unable to enter the country directly for employment but must come in with a different visa such as a student one (Boese et al 2013). They are also more likely to have to expend considerable resources in gaining registration and use recruiting agents to gain a job.…”
Section: Skilled Reproductive Sectorsmentioning
confidence: 98%
“…7 So whilst from 2001 to 2006 over 22,000 new work permits were granted for this category, this figure had dropped to 1005 in 2007 and only five new work permits were granted in 2008. Similarly in Australia, carers have not qualified since 2009 under the minimum salary levels demanded by the temporary migration programmes aimed at skilled labour (Boese et al 2013).…”
Section: Migration Regimes and Changing Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathways from temporariness to permanence are, as seminal work by one of this SpeciaI Issue's authors has shown, seldom explicit or guaranteed, leading to 'long term temporariness' and ongoing insecurity (Mares 2016). The insecurities associated with 'staggered pathways' are manifold, ranging from increased vulnerability to exploitation by employers (Boese et al 2013) to the frequent need for temporary visa holders to adjust their life and education goals (Robertson and Runganaikaloo 2014). Recent research on these experiences has called into question the common assumption of temporary migrants as a category of migrants in control of their migration pathway (Boese and Macdonald 2016).…”
Section: Temporary Migrants In Australiamentioning
confidence: 99%